Effects of Solid Retention Time (SRT) on Sludge Characteristics in Enhanced Biological Phosphorus Removal (EBPR) Reactor - Li, N. (Array, 2008)
Summary: This study investigated the effects of solid retention time (SRT) on sludge characteristics and operational performance in enhanced biological phosphorus removal (EBPR) reactor. The results showed that the reactor operated at SRT of = 8.3 d could achieve phosphate removal efficiency > 90 % and SVI < 100 mL g–1. In comparison, increasing SRT to = 16.6 d led to a decrease of phosphate removal ( < 85 %) and an increase of SVI value (160 mL g–1), implying a performance degradation and worse settleability of the sludge. In both cases, chemical oxygen demand (COD) removal was observed stable in terms of overall efficiency of = 90 %. Denaturing gradient gel electrophoresis (DGGE) profiles of sludge revealed a good phylogenetic relationship of sludge with different SRTs. However, the predominant population of community appeared to vary. Especially, the appearance of filamentous microorganisms at longer SRT may be responsible for worse performance and sludge settleability of EBPR system